A comparative review of current topical antibiotics for impetigo. Issue 6 (3rd June 2021) - Galindo, Eugenio; Hebert, Adelaide A
ABSTRACT: Introduction: Impetigo is a superficial bacterial skin infection largely affecting the pediatric population. The objective of this review is to provide a comparison of mechanism of action, efficacy and safety of the available topical antibiotics for impetigo. Areas covered: Randomized clinical trials that evaluated the use of topical antibiotics for treatment of impetigo were included. Two thousand eighty-nine studies were initially identified, and five randomized clinical trials met the criteria for further analysis. Expert opinion: Topical antibiotics had greater resolution of impetigo in comparison to vehicle in these pivotal clinical trials. Adverse events were minimal, with the most common being pruritus at the application site. Cost or insurance coverage may be a limiting factor in choosing the best therapeutic agent, with mupirocin ointment having the lowest cost. Mupirocin has shown clinical efficacy against MRSA but a bacterial culture is recommended to rule out resistance. Ozenoxacin and retapamulin are effective alternatives but may entail higher cost. Retapamulin is indicated for lesions of impetigo that are colonized by MSSA and streptococcus S. pyogenes but not MRSA based on clinical efficacy of phase III trials. Fusidic acid, available in other countries, is a non-FDA approved medication although rising resistance rates represent a growing concern.